The Cross-Cultural Validity of Post-Traumatic Stress Disorder and Post-Traumatic Stress Symptoms in the Indian Context: A Systematic Search and Review - Gilmoor, Andrew Roderick; Adithy, Adithy; Regeer, Barbara (Frontiers in Psychiatry, 2019)
Background: The cross-cultural validity of the construct of Post-Traumatic Stress Disorder (PTSD) has been a life-long debate in the field of trauma. Its validation in a setting such as India—a nation prone to considerably traumatic events such as conflict, natural disasters and sexual violence against women—warrants exploration. Objective: To describe how PTSD and Post-Traumatic Stress Symptoms (PTSS) is conceptualized in the Indian context by systematically examining the evidence of studies that investigate PTSD and PTSS in India. Methods: A systematic search in PubMed, Web of Science and Science Direct yielded a total of 56 studies that discussed one or multiple aspects of PTSD and PTSS in India. Data relating to types of events, populations, diagnostic tools, manifestations, and interventions were extracted and analyzed. Results: 11/29 Indian states and 2/7 union territories were represented in the 56 included studies, with most studies (n=21) originating from Tamil Nadu. Natural Disasters (n=28), War/Conflict (n=10), and Medical conditions (n=7), were the top three most commonly investigated traumatic events. The majority of studies focused on entire communities (n=16), while children and adolescents made up the second largest group (n=14). Less attention was paid explicitly to male (n=3) or female (n=4) victims. Twenty five different methods for screening for PTSD were identified with the most common being the impact of events scale (n=14). The majority of studies reported the screening and clinical diagnosis of PTSD by professional health care providers (n=24). Abuse scored the highest average prevalence of PTSD at 52.3% while the lowest was 16.4% due to man-made accidents. Overall there was a lack of assessment on trauma-specific interventions, though psychosocial support was the most commonly mentioned intervention. Conclusions: results indicate diversity in approaches for identifying, measuring and treating PTSD and PTSS in the Indian population and how sociocultural norms influence its manifestation in this population. Future research calls for the development of culturally sensitive approaches to identifying and addressing PTSD and PTSS in India.